Economic effect of carbon storage due to forest management intensification: analysis and forecast for the Republic of Karelia - A. A. Vysokikh-Al-Yasiri (Russian Journal of Economics and Law)
Objective: to assess the economic potential of carbon storage for a group of companies in the Republic of Karelia in the context of intensive forest management.Methods: SWOT analysis; assessment of a forest management project according to the VM10 international methodology, Verified Carbon Standard 2016 and forecast of revenues from selling carbon units.Results: the potential of Russian forest management in the context of the Paris Agreement is not disputed, but the assessment of the economic potential of carbon storage of individual economic entities at the moment remains open for discussion. The study estimates the effect of selling carbon units from forest management intensification projects, taking into account the maximum lease term for the area of 2.25 million hectares. This effect can reach an average of 23 million rubles per year from 2023 to 2034 and an average of 42 million rubles per year from 2023 to 2050, excluding the capital costs of logging and preparation, validation, verification and registration of the climate project, and field observations to ensure monitoring. The study proves that long-term investments in forest management intensification and a longer period of the climate project can lead to higher income per hectare from selling carbon units.Scientific novelty: it consists in the economic evaluation of regulatory restrictions on the price of carbon unit for forest climate projects, taking into account the maximum lease term stipulated by national legislation. The obtained results substantiate the economic challenges associated with the current regulations and provide information on the variability of project efficiency depending on the selected term of its implementation.Practical significance: the main results of the research can be used in the practical activity of economic entities, as well as by the bodies forming the policy of forest management.